2022
DOI: 10.1039/d1ta08968d
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped porous carbon fiber/vertical graphene as an efficient polysulfide conversion catalyst for high-performance lithium–sulfur batteries

Abstract: A freestanding sulfur cathode based on nitrogen-doped porous carbon fiber/vertical graphene (NF@VG) composites is proposed to effectively boosts the catalytic conversion kinetics of polysulfides and inhibit the shuttle effect of polysulfides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Besides, more and more studies have also reported that doping of heteroatoms [such as nitrogen ( Cheng et al, 2022 ; Lin et al, 2022 ), phosphorus ( Liu et al, 2021b ; Huang et al, 2021 ), sulfur ( Li et al, 2018 ; Zhang et al, 2020 ), boron ( Yang et al, 2014 ; Eroglu et al, 2020 ) etc.,] in carbon materials can result in the enhancement of conductivity and electrochemical activity of the material. It has been proven that nitrogen-doped carbon materials can improve the interaction between sulfur and the carbon matrix, assist in inhibiting the shuttle effect of polysulfides, and then enhance the interaction between nitrogen doping site functional groups and polysulfides ( Jing et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, more and more studies have also reported that doping of heteroatoms [such as nitrogen ( Cheng et al, 2022 ; Lin et al, 2022 ), phosphorus ( Liu et al, 2021b ; Huang et al, 2021 ), sulfur ( Li et al, 2018 ; Zhang et al, 2020 ), boron ( Yang et al, 2014 ; Eroglu et al, 2020 ) etc.,] in carbon materials can result in the enhancement of conductivity and electrochemical activity of the material. It has been proven that nitrogen-doped carbon materials can improve the interaction between sulfur and the carbon matrix, assist in inhibiting the shuttle effect of polysulfides, and then enhance the interaction between nitrogen doping site functional groups and polysulfides ( Jing et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…N-doped carbon materials, such as N-doped porous carbon, [57,58] N-doped graphene, [59] and N-doped carbon fibers, [60] have been reported for enhanced SRR kinetics. N-doping enhances the electrical conductivity and chemical adsorption toward polysulfides, promoting the convention kinetics of sulfur species through catalytic effects.…”
Section: Carbonmentioning
confidence: 99%
“…This physical confinement and chemical anchoring help prevent the loss of soluble lithium polysulfides, reducing the notorious “shuttle effect”. Further, N-doped carbon can improve the sulfur cathode cycle stability and promote Li + diffusion, resulting in increased charge transfer from polysulfide species to N-doped substrates through Li atoms. , …”
Section: Introductionmentioning
confidence: 99%
“…The interconnected network of PAN-derived CNFs provides physical confinement and anchoring sites for sulfur species within the cathode. Also, the N-doped carbonaceous materials with active sites, such as pyridinic-N, pyrrolic-N, and graphitic-N, are effective techniques for polysulfide chemisorption . This physical confinement and chemical anchoring help prevent the loss of soluble lithium polysulfides, reducing the notorious “shuttle effect”.…”
Section: Introductionmentioning
confidence: 99%